Pedogeomorfologia, morfometria de bacia hidrográfica e uso dos solos como fatores condicionantes de qualidade e quantidade de água na apa do Rio Uberaba, triângulo mineiro - VIANNA, Nathalia Barbosa (2018)
The watershed is considered a management and planning unit, for this reason it is commonly used in environmental studies. Thus, the study was carried out in the watershed of the Saudade stream, located in the Environmental Protection Area at Uberaba river, one sources of public water supply for the municipality of Uberaba, Triângulo Mineiro-Brazil region. Two study lines were used: the hydrological and the pedogeomorphological components, which supported the sampling and analysis of water and soil, and consequently, several methods to understand the natural elements that compose this landscape in a systemic way. The results showed a watershed with balanced functioning in front of its main natural variables and the water quality classified as good. Besides, the relief influence in the soils conditioning, and consequently, of its uses in the studied area.